Dynamic Soil-Structure Interaction of Multi-Story Buildings using the Finite Element Method and Minimax Probability Machine Regression - Kar, Saurav Shekhar; Athawale, Anupama Arunkumar; Bhushan, Mani; Roy, Lal Bahadur (Engineering, Technology & Applied Science Research, 2023)
Soil-Structure Interaction (SSI) issues are some of the most critical problems encountered in the design of structures prone to earthquake shaking. The damage caused by an earthquake mainly depends on the interaction between soil and structure. In this study, the effect of dynamic SSI on a multi-story building is examined using two methods, Finite Element Method (FEM) and Minimax Probability Machine Regression (MPMR). The MPMR was used to develop a model based on the input and output database generated from the FEM model. The performance comparison of these two models shows a good correlation. The MPMR model significantly reduced the computational time and can thus be utilized as a substitute for determining the response quantities.